Тhe role of Turkic loan lexica in formation of Arabic phraseologies (Journal of Oriental Studies, 2016)
this article explores the role of turkic loan lexica in formation of arabic phraseologies. turkisms exist in all spheres of arabic world. although they are not the active part of word formation of arabic language, still they play important role in combination with arabic words.
Keywords: phraseologies; arabic language; turkic loan words